Distillation Processes (IntechOpen, 2023)
Distillation is an important separation technique that has been used for many centuries to exploit the volatility differences between components in a mixture. The distillation process has many variations and applications. This book includes two sections on desalination and reactive distillation. It discusses desalination in the processes of solar and membrane distillation, with a focus on the reduction of energy costs to obtain potable water. It also discusses reactive distillation, which can be used in some cases to reduce the power duty in the separation process by using the reaction heat directly in the separation. The book includes cases of mathematical modeling, simulation, and optimization of the distillation process.